HUBUNGAN KALORI SARAPAN PAGI DENGAN KONSENTRASI BELAJAR PADA MAHASISWA KEDOKTERAN TAHUN KEDUA UNIVERSITAS ABDURRAB - Huda Marlina Wati; Fadila Rizki Yani (LPPM Universitas Abdurrab, 2025)
Concentration is attention, thoughts and actions on an object by eliminating all unrelated things. Concentration as the basis for receiving lessons and as an indicator of assessing success in the learning process. One of the factors that influences concentration is the fulfillment of nutrients in the morning or breakfast. People in Indonesia still often skip breakfast, this may be because they are not used to having breakfast. The change in lifestyle in these students requires time to adapt. In addition, these second-year students have a busy schedule and various practicum class that were followed, so they were prone to skipping breakfast which will have an impact on student learning concentration. This study uses an analytical observational study type with a cross-sectional method. The sampling technique used is total sampling on second-year medical students. Data will be analyzed using the Pearson correlation test if it meets the parametric requirements and data will be analyzed using the Spearman correlation test if it does not meet the parametric requirements. This study aims to analyze the relationship between breakfast calories and learning concentration in students of the Medical Student Abdurrab University and to analyze the difference in concentration levels during breakfast and when not having breakfast in students of the Medical Education Study Program at Abdurrab University. The results of this study indicate that there is no relationship between the relationship between breakfast calories and the concentration of second-year students of the Faculty of Medicine, Abdurrab University with a p value of 0.14.